Usage of mobile payments in Point-Of-Sale transactions - Polasik, Michał; Przenajkowska, Karolina; Starogarska, Ewa; Meciejewski, Krzysztof (Wykorzystanie płatności mobilnych w transakcjachw punktach sprzedaży, 2011)
In the paper the analysis of prospects of Near Field Communication (NFC) mobile payments in Point-Of-Sale transactions has been carried out. According to empirical study, NFC is one of the quickest and the most convenient method of payment for the Points-Of-Sale. Furthermore, it opens opportunities to integrate payments with other services and functions available on a mobile phone. Main obstacles are the low level of acceptance among merchants and limited number of mobile devices equipped with NFC technology. As a result,NFC payments have not been commercially deployed on a large scale except Japan and South Korea. However, NFC payments and contactless cards use the same contactless POS terminals network, what generates the synergic effect. Therefore, NFC mobile payments may surprise the market and develop more rapidly than expected
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 227-239
Keywords: mobile payments; NFC; proximity & remote payments; POS transactions